Mental Health of Prison Inmates During the COVID-19 Pandemic: A Systematic Review - Francisco Javier González-Riera; Juan Jesús García-Iglesias; Regina Allande-Cussó; Carlos Ruiz-Frutos; Carlos Ruiz-Frutos; Luciano Rodríguez-Diaz; Juana María Vázquez-Lara; Francisco Javier Fernández-Carrasco; Javier Fagundo-Rivera; Juan Gómez-Salgado; Juan Gómez-Salgado (Frontiers Media S.A., 2024)
ObjectivesThe aim of this study was to comprehensively assess how COVID-19 affected the levels of different mental health variables in prison inmates.MethodsA systematic review was conducted following the PRISMA format in the Pubmed, Scopus, Web of Science, PsycINFO, and ScienceDirect electronic databases between August and September 2023. Methodological quality was assessed using the critical appraisal tools for studies of the Joanna Briggs Institute.ResultsThirteen studies were included. The studies found increased levels of stress, anxiety, fear, depression, and negative emotions associated with lack of information about the pandemic and isolation leading to reduced social interaction. In addition, lack of access to common recreational spaces, limited access to support resources, especially mental health resources, fear of contracting the virus, and lack of trust in prison staff and in themselves to be protected were identified.ConclusionFurther research may be necessary in prison populations with added vulnerability, such as the elderly, women, transgender and non-binary persons, to determine specific interventions, after assessing the prevalent psychological sequelae. Prevention strategies and mental health promotion are also encouraged.